Optical Solitons for the Dispersive Concatenation Model: Undetermined Coefficients (Contemporary Mathematics, 2023)
This paper recovers optical solitons to the dispersive concatenation model that is studied with Kerr law of self-phase modulation. The method of undetermined coefficients is the adopted integration algorithm, enabling this retrieval possible. A full spectrum of optical solitons is recovered. The parameter constraints for the existence of the solitons, that naturally emerge during the course of their derivation, are also presented. The practical applications of this research include advancements in optical communication, nonlinear optics, and optical signal processing, as well as the potential for optimizing optical soliton-based technologies. In our current work, we have achieved the following novel findings: optical soliton recovery, integration algorithm innovation, and parameter constraints.
Keywords: concatenation, solitons, dispersion, parameter constraints